Thermodynamic characteristics of CO2 adsorption on β-cyclodextrin based porous materials: Equilibrium capacity function with four variables - Du, Yarong; Geng, Yuhan; Guo, Tianxiang; Zhang, Runan; Zhang, Yonghe; Wang, Xilai; Han, Zhonghe (Case studies in thermal engineering, 2022)
This work focuses on establishing a kind of extended adsorption model equation including four variables relevant to preparation conditions (activation temperature and heating rate) except adsorption situations (adsorption temperature and adsorption pressure). And the equation is used for thermodynamic analysis of CO2 adsorption on a promising cyclodextrin based porous material. Novelty, those isotherms of CO2 adsorption on the porous materials prepared at different activation temperatures and heating rates are experimentally obtained to investigate the effects of activation temperature and heating rate on CO2 adsorption. Then the parameters of the model equation are quantified based on 589 data points from the isotherms by the least squares regression method combined with the steepest descent mode. Research results indicate that high performance for CO2 uptake appears on the porous material prepared at high activation temperature and low heating rate. Differently with the previous studies, the adsorption site energy distribution is found to exhibit an asymmetrical peak and the peak site energy increases with an increase of activation temperature but the decrease of heating rate. Moreover, a series of interesting phenomena of those thermodynamic state parameters via adsorption temperature and pressure are verified based on both extended Slip model and D-R model, which have not been reported before. [Display omitted] •A promising adsorbent of CO2 was prepared from β-cyclodextrin by thermal activation.•The capacity equations including four variables were newly found.•Mass and energy transfer during CO2 adsorption based on isothermal-isobaric conditions was completely revealed.•The thermodynamic characteristics of CO2 adsorption under isothermal-isobaric conditions were systematically investigated.•A series of interesting phenomena related to the effects of temperature and pressure were verified.